2021
DOI: 10.1088/1755-1315/807/2/022070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization edible films of sago with glycerol as a plasticizer

Abstract: Sago is one of the local food districts of Sangihe archipelago, but its use is still limited to traditional products. Edible film of sago starch is one of the alternative products for increasing the added value of this commodity as well as an environmentally friendly packaging material. The research aims to obtain edible film from sago starch using CMC and glycerol. Edible film processing was carried out by mixing 5% sago starch, and CMC 0.5% w/v and glycerol variation 1; 1.25; 1.5; 1.75; 2; 3.75; (%v/v) at 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
5
1
2
Order By: Relevance
“…Yanti et al / agriTECH, 44 (1) 2024, 9-16 plasticizers were easily interpolated between polymer chains, creating a "cross-linker" effect that bring down the free volume and the movement of polymer segments, leading to reduced mechanical strength and Young's Modulus. The addition of glycerol as a plasticizer in edible films can enhance elasticity and elongation at break (Dick et al, 2015;Lintang et al, 2021). However, in this study, glycerol added with edible films increased elasticity but decreased elongation percentage.…”
Section: Mechanical Characteristics Of Edible Filmcontrasting
confidence: 59%
See 1 more Smart Citation
“…Yanti et al / agriTECH, 44 (1) 2024, 9-16 plasticizers were easily interpolated between polymer chains, creating a "cross-linker" effect that bring down the free volume and the movement of polymer segments, leading to reduced mechanical strength and Young's Modulus. The addition of glycerol as a plasticizer in edible films can enhance elasticity and elongation at break (Dick et al, 2015;Lintang et al, 2021). However, in this study, glycerol added with edible films increased elasticity but decreased elongation percentage.…”
Section: Mechanical Characteristics Of Edible Filmcontrasting
confidence: 59%
“…Similarly, Ballesteros-Mártinez et al, (2020) and Ismaya et al )2021) reported that the addition of glycerol at certain concentrations in edible films could enhance their mechanical properties. Excess concentrations might reduce the intermolecular forces among the film matrix components, leading to a decrease in the stability of the solid dispersion system and a reduction in mechanical strength (Jafarzadeh et al, 2018;Lintang et al, 2021).…”
Section: Mechanical Characteristics Of Edible Filmmentioning
confidence: 99%
“…In this case, the addition of glycerol as a plasticizer to PVA has resulted in a decrease in the WVTR. This indicates that the plasticizer has improved the material's ability to resist the passage of water vapor, making it more suitable for applications requiring water vapor barrier properties [25,26]. The WVTR results demonstrate that the incorporation of glycerol as a plasticizer in PVA-G reduces the permeability of the material to water vapor.…”
Section: Barrier Propertiesmentioning
confidence: 92%
“…The treatments of the present study are as follows: dipping in pure water (control), edible coating (EC) and edible coating enriched with laurel essential oil (EC+LEO). The method of edible coating preparation was modified from several previous studies (Casariego et al 2008;Lintang et al 2021;Sapper and Chiralt 2018). The method used is as follows: corn starch (2% w/v) (Ribeiro et al 2007;Sapper and Chiralt 2018), glycerol (0.5% v/v) (Casariego et al 2008;Lintang et al 2021) and tween 80 (1.0%) (Sigma-Aldrich, Germany) were mixed in distilled water (2 L) and heated up to 90-95 °C.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The method of edible coating preparation was modified from several previous studies (Casariego et al 2008;Lintang et al 2021;Sapper and Chiralt 2018). The method used is as follows: corn starch (2% w/v) (Ribeiro et al 2007;Sapper and Chiralt 2018), glycerol (0.5% v/v) (Casariego et al 2008;Lintang et al 2021) and tween 80 (1.0%) (Sigma-Aldrich, Germany) were mixed in distilled water (2 L) and heated up to 90-95 °C. The higher concentrations of glycerol were suggested to decrease the wettability and adhesion coefficients of the edible coatings (Casariego et al 2008).…”
Section: Experimental Studiesmentioning
confidence: 99%